Development of an educational program: promoting sustainability in consumer laundry behavior - Coats, Mary, author; Yan, Ruoh-Nan, advisor; Park, Juyeon, committee member; Dunbar, Brian, committee member (Colorado State University. Libraries, 2014)
Sustainability in business and personal living practices has grown over the past several years and is continuing to develop. Consumption in the apparel industry causes a significant impact on the environment and utilizes unsustainable practices for clothing production, use, and disposal. The use phase of the clothing lifecycle has been established to be the most energy intensive and environmentally impactful. The purpose of this research was to further the understanding of laundry behaviors of consumers and between genders and to test whether education on more sustainable laundry behaviors influenced sustainable laundry behavioral intentions. The Sustainable Laundry Behavior Model was developed to help understand the relationship between knowledge, attitude, and behavior in regards to sustainable laundering. The current levels of sustainable laundry knowledge, attitudes toward the environment, attitudes toward sustainable laundry behavior, and sustainable laundry behavioral intentions were measured among young adult college students. An educational program was also developed and tested among the participants. The methodology for this research utilized three phases including a focus group, a pre-educational survey and educational program, and a post-educational survey. Results described participants' current levels of sustainable laundry knowledge, attitudes toward the environment, attitudes toward sustainable laundry behavior, and laundry behaviors. Gender differences were evident in a few items that were tested. Results showed improved laundry knowledge in the area of knowledge of action strategies after the educational program, although knowledge of issues remained consistent between the pre-educational and post-educational surveys. Sustainable laundry behaviors improved after the educational program, suggesting its success. Results suggested that sustainable laundry knowledge influenced attitudes toward the environment and attitudes toward sustainable laundry behavior. Results also suggested that attitudes toward sustainable laundry behavior influenced future intentions for sustainable laundry behavior and future intentions for willingness and ability to practice sustainable laundry behavior.
Keywords: fashion industry; sustainable laundry behavior; sustainability; laundry